CAMP: From Long-Range Second Messenger to Nanodomain Signalling. (February 2018) - Musheshe, Nshunge; Schmidt, Martina; Zaccolo, Manuela
Abstract : How cAMP generates hormone-specific effects has been debated for many decades. Fluorescence resonance energy transfer (FRET)-based sensors for cAMP allow real-time imaging of the second messenger in intact cells with high spatiotemporal resolution. This technology has made it possible to directly demonstrate that cAMP signals are compartmentalised. The details of such signal compartmentalisation are still being uncovered, and recent findings reveal a previously unsuspected submicroscopic heterogeneity of intracellular cAMP. A model is emerging where specificity depends on compartmentalisation and where the physiologically relevant signals are those that occur within confined nanodomains, rather than bulk changes in cytosolic cAMP. These findings subvert the classical notion of cAMP signalling and provide a new framework for the development of targeted therapeutic approaches. Highlights: Refinements of fluorescence-based imaging methods for real-time detection of cAMP signals in intact cells are providing novel insight into the subcellular organisation of this complex and multifunctional signalling pathway Compartmentalisation of cAMP signals appears to be more extreme than previously thought. Evidence is emerging that physiologically relevant cAMP/protein kinase A (PKA) signals are those constrained within subcellular compartments with submicroscopic dimension. A complex pattern comprising multiple cAMP signals with distinct amplitude and kinetics and with a nonometre range of action can be generated by the activation of an individual G-protein-coupled receptor (GPCR). The nanoheterogeneity of cAMP/PKA signals is required for fine-tuning of cellular function and is altered in animal models of disease.